Phonons and hybrid modes in the high and low temperature far infrared dynamics of hexagonal TmMnO3 - Massa, Nestor Emilio (2014)
We report on temperature dependent TmMnO3 far infrared emissivity and reflectivity spectra from 1910K to 4K. At the highest temperature the number of infrared bands is lower than that predicted for centrosymmetric P63/mmc ( ) D6h 4 (Z = 2) space group due to high temperature anharmonicity and possible defect induced bitetrahedra misalignments. On cooling, at ~1600±40K, TmMnO3 goes from non-polar to an antiferroelectric–ferroelectric polar phase reaching the ferroelectric onset at ~700K. Room temperature reflectivity is fitted using 19 oscillators and this number of phonons is maintained down to 4K. A weak phonon anomaly in the band profile at 217 cm−1 (4K) suggests subtle Rare Earth magneto-electric couplings at ~TN and below. A low energy collective excitation is identified as a THz instability associated with room temperature eg electrons in a d-orbital fluctuating environment. It condenses into two modes that emerge pinned to the E-type antiferromagnetic order hardening simultaneously down to 4K. They obey power laws with TN as the critical temperature and match known zone center magnons. The one peaking at 26 cm−1, with critical exponent β=0.42 as for antiferromagnetic order in a hexagonal lattice, is dependent on the Rare Earth ion. The higher frequency companion at ~50 cm−1, with β=0.25, splits at ~TN into two peaks. The weaker band of the two is assimilated to the upper branch of the gap opening in the transverse acoustical (TA) phonon branch crossing the magnetic dispersion found in YMnO3. (Petit et al 2007 Phys. Rev. Lett. 99 266604). The stronger second band at ~36 cm−1 corresponds to the lower branch of the TA gap. We assign both excitations as zone center magneto-electric hybrid quasiparticles, concluding that in NdMnO3 perovskite the equivalent picture corresponds to an instability which may be driven by an external field to transform NdMnO3 into a multiferroic compound by perturbation enhancing the TA phonon–magnetic correlation.